2022
DOI: 10.21203/rs.3.rs-2379583/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenic lymphangiogenesis promotes autoimmune valvular carditis

Abstract: Rheumatic heart disease (RHD) is a major cause of valvular heart disease in developing nations. Endothelial cells (ECs) are considered crucial contributors to RHD, but greater insight into contributing mechanisms is needed. Cdh5-driven EC lineage tracing in the K/B.g7 mouse model of autoimmune valvular carditis revealed new capillary lymphatic vessels that develop from valve surface endothelial cells during the progression of disease. Human rheumatic valves contained similar lymphatics. Unsupervised clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Lymphangiogenesis has been demonstrated also in cardiac valves in valvulopathies. 3,4 Furthermore, recent clinical studies have demonstrated that cardiac lymphangiogenesis occurs in patients experiencing primary or secondary hypertrophic or dilated cardiomyopathy. 5,6 Lymphatic vessels, located in the epicardium of human fetal hearts, are associated mainly with coronary arteries that produce VEGF-C (vascular endothelial growth factor C), 7 essential for coronary lymphangiogenesis during development.…”
Section: See Cover Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Lymphangiogenesis has been demonstrated also in cardiac valves in valvulopathies. 3,4 Furthermore, recent clinical studies have demonstrated that cardiac lymphangiogenesis occurs in patients experiencing primary or secondary hypertrophic or dilated cardiomyopathy. 5,6 Lymphatic vessels, located in the epicardium of human fetal hearts, are associated mainly with coronary arteries that produce VEGF-C (vascular endothelial growth factor C), 7 essential for coronary lymphangiogenesis during development.…”
Section: See Cover Imagementioning
confidence: 99%
“…Lymphangiogenesis has been demonstrated also in cardiac valves in valvulopathies. 3,4 Furthermore, recent clinical studies have demonstrated that cardiac lymphangiogenesis occurs in patients experiencing primary or secondary hypertrophic or dilated cardiomyopathy. 5,6…”
mentioning
confidence: 99%